Development of a Novel Molecularly Imprinted Polyvinylimidazole/Functionalized Carbon Black Nanocomposite‐based Paste Electrode for Electrochemical Sensing of Imazethapyr in Rice Samples. Issue 5 (7th January 2022) - Angelis, Pedro Nunes; Casarin, Juliana; Gonçalves Júnior, Affonso Celso; Rocha, Luana Rianne; Prete, Maiyara Carolyne; Tarley, César Ricardo Teixeira
Abstract: This paper reports the development of a simple electroanalytical method for imazethapyr (IMT) determination in rice samples based on molecularly imprinted polymer and functionalized carbon black paste electrode (MIP‐fCBPE). Carbon black (CB) was functionalized by the insertion of oxygenated functional groups upon acid treatment with HNO3 and H2 SO4 . The functionalized carbon black (fCB) presented higher performance for IMT determination than the CB without functionalization. The insertion of molecularly imprinted polyvinylimidazole (MIP‐VN) in the fCBPE promoted a significant increase in the cathodic peak current even at low proportions (7.5 % w/w) due to the specific binding sites for IMT recognition. For IMT determination, DPV parameters were optimized by the Doehlert matrix applying 0.1 V for 60 s as pre‐treatment in acetate buffer solution (pH 3.0) as supporting electrolyte. The proposed method showed low limit of detection (0.03 μmol L −1 ), a wide linear range (0.10–70.00 μmol L −1 ), and good precision in terms of repeatability of intraday measures (RSD%=3.6). The method was applied in rice samples after microwave‐assisted extraction of IMT and the accuracy of the method was evaluated by addition/recovery assays (96.3–105.7 %), being statistically attested using HPLC‐DAD as reference technique. Abstract :